Bank Mergers, Operational Efficiency, and Market Stability: A Cross-Country Analysis - Alroomi, Azzam (Journal of Posthumanism, 2025)
This paper examines three decades of banking sector M&As across 26 countries through a case study to investigate M&A effects on market stability and operational efficiency as well as transaction value changes. The paper utilizes linear regression models with fixed effects to discover patterns between regulatory conditions along with economic factors and capital allocation preferences which shape M&A results in different market classes. Statistics show that mature economies tend to perform M&A transactions with increased steadily whereas these actions improve operational effectiveness and exist under solid regulatory frameworks and comprehensive financial systems. The regulatory needs of emerging markets require specialized measures because these countries deal with ineffective financial instruments as well as volatile market conditions. The variations in capital structure choices demonstrate that developed areas use equity financing more often than developing areas whose preference is debt financing which causes more financial hazards. Specific banking regulation adjusted to local circumstances can substantially augment the beneficial effects that M&A activities produce on banking success as well as economic strength.